(3cJGH JhMjO GdHGQjs - (3GdSjhQj, GdMdj, GdCSOj, GdebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826(3g`s
(3ChdgG (B:s
(3SHMGfc Gddge hGLH GdhLhO heHOC ZGjI cd ehLhO(B... (3CeG HYO, adeG cGf Yde GdcdGe ef Hjf gPg GdYdhe Ch Kb HQgGfG(B... (3ahYOJ HYV GdaVdGA GdCPcjGA hGdCdHGA GdYdeGA HTQMgG(B...s
(3BNQgG (B:s
(3NJe GdeUfa QMeg Gddg QSGdJg gPg HgPg GdfUjMI heVehfgG GdMK Ydi YHGOI Gddg(B... (3hJPcjQ hJLOjOG dfYeg dOjge aef bGe HPdc abO aGR ahRG YXjeG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B470s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds